2010
DOI: 10.1029/2009ja014575
|View full text |Cite
|
Sign up to set email alerts
|

Possible relations between meteors, enhanced electron density layers, and sporadic sodium layers

Abstract: [1] In this paper, we studied the possible relations between incoming meteors, sporadic E (Es) layers, and sporadic (or sudden) sodium atom layers (SSLs) using the data from the FORMOSAT-3/COSMIC constellation, a meteor radar (Wuhan, 31°N, 114°E), and a sodium fluorescent lidar (Hefei, 31.8°N, 117.3°E). From a statistical point of view, a seasonal dependence of SSL correlates well with the annual variation of Es and is also consistent with seasonal meteor deposition except for February and March. It suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 54 publications
2
59
1
Order By: Relevance
“…The identification of E s occurrence is different from paper to paper (Arras et al, 2008;Chu et al, 2014;Dou et al, 2010;Hocke et al, 2001;Wu et al, 2005;Yeh et al, 2012;Zeng and Sokolovskiy, 2010). Hocke et al (2001) and Dou et al (2010) derived E s occurrence from the fluctuations of RO inverted electron density profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of E s occurrence is different from paper to paper (Arras et al, 2008;Chu et al, 2014;Dou et al, 2010;Hocke et al, 2001;Wu et al, 2005;Yeh et al, 2012;Zeng and Sokolovskiy, 2010). Hocke et al (2001) and Dou et al (2010) derived E s occurrence from the fluctuations of RO inverted electron density profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have also indicated that gravity waves are vulnerable to breaking in the mesopause region (80-105 km) owing to the temperature inversion layer [Hauchecorne et al, 1987;Meriwether et al, 1998;Gardner et al, 2002;Williams et al, 2002]. Clemesha et al, 1999;Friedman et al, 2000;Dou et al, 2010;Xue et al, 2013]. And a less pronounced link, or absence of a link, between Es and SSL is observed below 95 km [Hansen and Von Zahn, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies Clemesha et al, 1999;Williams et al, 2007;Dou et al, 2010;Xue et al, 2013] have shown that SSLs are associated with sporadic E (Es) layers. Cox and Plane [1998] reported that Na + can …”
Section: Sporadic E Layer Mechanismmentioning
confidence: 99%
See 2 more Smart Citations